2022
DOI: 10.3390/ijerph19052981
|View full text |Cite
|
Sign up to set email alerts
|

(Not That) Essential: A Scoping Review of Migrant Workers’ Access to Health Services and Social Protection during the COVID-19 Pandemic in Australia, Canada, and New Zealand

Abstract: Migrant workers have been disproportionately affected by the COVID-19 pandemic. To examine their access to health services and social protection during the pandemic, we conducted an exploratory scoping review on experiences of migrant workers in three countries with comparable immigration, health, and welfare policies: Australia, Canada, and New Zealand. After screening 961 peer-reviewed and grey literature sources, five studies were included. Using immigration status as a lens, we found that despite more incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…A lack of engagement and collaboration with ethnic minority communities, government advisory groups and community member voices within policy and decision-making was cited as a significant challenge to effectively communicating and engaging with communities during the COVID-19 pandemic 13 25 30 37 40. For example, a qualitative review of six pandemic plans in Australia found significant gaps in engaging with ethnic minority communities, specifically a lack of focus on the need for engagement activities in all the plans assessed 13…”
Section: Resultsmentioning
confidence: 99%
“…A lack of engagement and collaboration with ethnic minority communities, government advisory groups and community member voices within policy and decision-making was cited as a significant challenge to effectively communicating and engaging with communities during the COVID-19 pandemic 13 25 30 37 40. For example, a qualitative review of six pandemic plans in Australia found significant gaps in engaging with ethnic minority communities, specifically a lack of focus on the need for engagement activities in all the plans assessed 13…”
Section: Resultsmentioning
confidence: 99%
“…Newcomers to a country, whether by legal or illegal means, are often less able to access health care than permanent residents of a country. 47,48 A significant barrier to accessing current prenatal diagnosis and therapy is the associated financial burden. Despite ACOG guidelines recommending prenatal testing for all pregnant individuals and research evidencing the substantial health benefits and economic advantages of doing so, not all have access due to insurance access challenges or inability to pay out of pocket.…”
Section: What Are the Barriers To Care?mentioning
confidence: 99%
“…Immigration status is another factor sometimes related to social determinants of health that impacts access to health care. Newcomers to a country, whether by legal or illegal means, are often less able to access health care than permanent residents of a country 47,48 …”
Section: What Are the Barriers To Care?mentioning
confidence: 99%
“…Additionally, it is a significant step in improving the accessibility of migrant workers' public health welfare and promoting a more equitable health system for them. Health and health inequality are influenced by a variety of factors, including genetic and inherited factors, the physical environment, individual behavior and habit, as well as the provision and demand for public health services [43,44]. Consequently, risk management and equitization of public welfare can be used to intervene in health inequality.…”
Section: Mechanism Analysis Of Self-employment Affecting Health Inequ...mentioning
confidence: 99%